Dynamic characteristics of water spreading over laser-textured aluminum alloy surfaces; Colloids and Surfaces A: Physicochemical and Engineering Aspects; Vol. 603 - Kuznetsov G. V. Geny Vladimirovich; Feoktistov D. V. Dmitriy Vladimirovich; Orlova E. G. Evgeniya Georgievna; Zykov I. Yu. Iliya Yurievich; Bartuli E. Erik; Raudensky M.; Zhuykov A. V. Andrey Vladimirovich (2020, 2020)
Title screen